Global population collapse in a superabundant migratory bird and illegal trapping in China. Issue 6 (8th June 2015) - Kamp, Johannes; Oppel, Steffen; Ananin, Alexandr A.; Durnev, Yurii A.; Gashev, Sergey N.; Hölzel, Norbert; Mishchenko, Alexandr L.; Pessa, Jorma; Smirenski, Sergey M.; Strelnikov, Evgenii G.; Timonen, Sami; Wolanska, Kolja; et al.
Abstract: Persecution and overexploitation by humans are major causes of species extinctions. Rare species, often confined to small geographic ranges, are usually at highest risk, whereas extinctions of superabundant species with very large ranges are rare. The Yellow‐breasted Bunting (Emberiza aureola) used to be one of the most abundant songbirds of the Palearctic, with a very large breeding range stretching from Scandinavia to the Russian Far East. Anecdotal information about rapid population declines across the range caused concern about unsustainable trapping along the species' migration routes. We conducted a literature review and used long‐term monitoring data from across the species' range to model population trend and geographical patterns of extinction. The population declined by 84.3–94.7% between 1980 and 2013, and the species' range contracted by 5000 km. Quantitative evidence from police raids suggested rampant illegal trapping of the species along its East Asian flyway in China. A population model simulating an initial harvest level of 2% of the population, and an annual increase of 0.2% during the monitoring period produced a population trajectory that matched the observed decline. We suggest that trapping strongly contributed to the decline because the consumption of Yellow‐breasted Bunting and other songbirds has increased as a result of economic growth and prosperity in East Asia. The magnitude and speed of the decline is unprecedented among birds with a comparable range size, with the exception of the Passenger Pigeon (Ectopistes migratorius), which went extinct in 1914 due to industrial‐scale hunting. Our results demonstrate the urgent need for an improved monitoring of common and widespread species' populations, and consumption levels throughout East Asia.